The VWF-GPIb axis in ischaemic stroke: lessons from animal models - Denorme, Frederik; De Meyer, Simon F. (Thrombosis and Haemostasis, 2016)
Stroke is a leading cause of death and long-term disability worldwide. Ischaemic stroke is caused by a blood clot that obstructs cerebral blood flow. Current treatment mainly consists of achieving fast reperfusion, either via pharmacological thrombolysis using tissue plasminogen activator or via endovascular thrombectomy. Unfortunately, reperfusion therapy is only available to a limited group of patients and reperfusion injury can further aggravate brain damage. Hence, there is an urgent need for better understanding of ischaemic stroke pathophysiology in order to develop novel therapeutic strategies. In recent years, the pathophysiological importance of von Willebrand factor (VWF) in ischaemic stroke has become clear from both clinical and experimental studies. In particular, binding of VWF to platelet glycoprotein Ib (GPIb) has become an interesting target for ischaemic stroke therapy. Recent insights show that inhibting the VWF-GPIb interaction could result in a pro-thrombolytic activity improving cerebral reperfusion rates and concurrently reducing cerebral ischaemia/reperfusion damage. This review gives an overview of the experimental evidence that illustrates the crucial role of the VWF-GPIb axis in ischaemic stroke.
Keywords: Stroke; animal models; thrombo-inflammation; von Willebrand factor; Glycoprotein Ib